2013
DOI: 10.3389/fpsyg.2013.00402
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in adult handwritten spelling-to-dictation

Abstract: We report an investigation of individual differences in handwriting latencies and number of errors in a spelling-to-dictation task. Eighty adult participants wrote a list of 164 spoken words (presented in two sessions). The participants were also evaluated on a vocabulary test (Deltour, 1993). Various multiple regression analyses were performed (on both writing latency and errors). The analysis of the item means showed that the reliable predictors of spelling latencies were acoustic duration, cumulative word f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Therefore, Roux et al suggested that central processing of the conflict generated by lexically specific and assembled spelling information for irregular words is not entirely resolved when peripheral processing begins. Furthermore, these results give rise to the possibility that higher order linguistic variables can affect peripheral processing (Bonin et al, 2013 ; Roux et al, 2013 ), which supports the view that activation cascades from central processing to peripheral processing in written word production.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, Roux et al suggested that central processing of the conflict generated by lexically specific and assembled spelling information for irregular words is not entirely resolved when peripheral processing begins. Furthermore, these results give rise to the possibility that higher order linguistic variables can affect peripheral processing (Bonin et al, 2013 ; Roux et al, 2013 ), which supports the view that activation cascades from central processing to peripheral processing in written word production.…”
Section: Introductionsupporting
confidence: 66%
“…Writing involves different processing levels from the intention of writing to the actual movement execution. The current view of speech production provides a general theoretical framework from which hypotheses specific to writing can be derived (Bonin et al, 1997 , 1998a , b , 2013 ; Rapp et al, 1997 ; Bonin and Fayol, 2000 ; Baus et al, 2013 ; Damian and Qu, 2013 ; Zhang and Wang, 2014 ). Recently, research in the field of written production has addressed the role of phonology codes in spelling or writing the names of pictures (Bonin et al, 2001 ; Afonso and Alvarez, 2011 ; Qu et al, 2011 ; Shen et al, 2013 ; Zhang and Wang, 2015 ), and these studies used writing latency as the dependent variable to uncover the planning process before writing execution.…”
Section: Introductionmentioning
confidence: 99%
“…However, less work has been devoted to understanding written production. The current views of speech production provide a general theoretical framework from which hypotheses specific to writing can be derived ( Bonin et al, 1997 , 1998a , b , 2013 ; Rapp et al, 1997 ; Bonin and Fayol, 2000 ; Baus et al, 2013 ; Damian and Qu, 2013 ; Zhang and Wang, 2014 ). In the work reported here, we investigated how orthographic codes are accessed from the conceptual/semantic level in writing using a picture–word interference (PWI) paradigm, which is an experimental paradigm that is popular in speech production (i.e., Schriefers et al, 1990 ; Starreveld and La Heij, 1995 , 1996a , b ; Damian and Martin, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…A central debate in the field is the contributions of orthographic and phonological codes (e.g., Qu et al, 2011 ; Bonin et al, 2013 ; Damian and Qu, 2013 ). Early theoretical accounts claimed that the retrieval of an orthographic representation was entirely dependent on the prior retrieval of phonological codes, which is called the OBLIGATORY phonological mediation hypothesis ( Geschwind, 1969 ; Luria, 1970 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the proposal that it is specifically the semantic-to-lexical connections (involved in “active” retrieval) that lead to interference, long-lasting semantic interference would not be observed since these connections are not used by the direct N-SM route. Alternatively, the failure to find semantic interference in written spelling to dictation could occur in a system that does not include a N-SM lexical process if the results are instead due to the interaction of the SM lexical and the sublexical routes, both of which are active in production including during written spelling to dictation (Bonin, Collay, Fayol, & Méot, 2005; Bonin et al, 2015; Bonin, Méot, Millotte, & Barry, 2013; Rapp et al, 2002; Tainturier & Rapp, 2001). The output of the sublexical route may constrain the selection of lexical representations via feedback from orthographic working memory (see discussion in the introduction for details).…”
Section: Discussionmentioning
confidence: 99%